Cloning and Expression of the Haemagglutinin-neuraminidase Gene of Newcastle Disease Virus Strain Af2240 Lnto Eschericia Coli - Sudin, Sudani (1997)
A 1815 bp sequence of the open reading frame (ORF) of the haemagglutinin-neuraminidase (HN) gene of velogenic-viscerotropic Newcastle disease virus (NDV) strain AF2240 was amplified reaction (PCR) using primers SI (5'CACCAATAGCAGACTCCA3') and S2 (5'CCTTGGCATTGCAGAAG3'). Both primers had dUMP extensions which allowed direct cloning of the amplified product into the pAMP1 vector, which also has the complementary protruding termini.The recombinant plasmid was transformed into competent Eschericia coli strain DH5u. A total of 174 transformants were obtained and the transformation efficiency was 3.8 x 10⁴ CFU/µg. The presence of the HN specific inserts in the transformants were detected by colony hybridization, Southern blotting and finally nucleotide sequence analysis. The HN protein was shown to be expressed as an unglycosylated protein of size 63.0 kDa which is comparable to that predicted from the nucleotide sequence. Thus, this shows that the HN protein was successfully expressed from the E. coli and the protein obtained could be used for further analysis.